Effects of heating rate on the evolution of bio-oil during its pyrolysis. (1st May 2018) - Xiong, Zhe; Wang, Yi; Syed-Hassan, Syed Shatir A.; Hu, Xun; Han, Hengda; Su, Sheng; Xu, Kai; Jiang, Long; Guo, Junhao; Berthold, Engamba Esso Samy; Hu, Song; Xiang, Jun
Highlights: Slow heating rates promote primary reactions during bio-oil pyrolysis. Fast heating rate promote the secondary cracking of vapor. A proposed reaction mechanism of bio-oil pyrolysis is provided. The characteristics of primary and secondary products varied with the heating rate. Abstract: Bio-oil from the fast pyrolysis of biomass can be converted to solid carbon materials, chemicals and syngas by various thermochemical conversion methods. As a first step in all of these processes, bio-oil undergoes drastic components changes due to its exposure to the elevated temperature. Understanding the effects of heating rate on bio-oil transformation during its pyrolysis is therefore crucial for effective utilization of bio-oil. In this study, a bio-oil sample produced from the fast pyrolysis of rice husk at 500 °C was pyrolyzed in a fixed-bed reactor at temperatures between 300 and 800 °C at three different heating rates: fast (≈200 °C/s), medium (≈20 °C/s), and slow (≈0.33 °C/s). In addition to the quantification of coke and tar yields, the tar was characterized with an ultraviolet (UV) fluorescence spectroscopy, a gas chromatography/mass spectrometer (GC/MS) and a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS). Our results indicate that slow heating rates promote polymerization of bio-oil components, particularly at low temperatures (<500 °C), resulting in higher primary coke yields than that of the fast heating rates. Decomposition reaction was found to be pronounced at fast heating rates, causing decreases in the tar yields and abundance of light compounds. The increases in the yields of the secondary coke, the formations of more condensed aromatic structures and macromolecules ( m / z > 500) were also promoted at fast heating rates via the more intense secondary reactions.